2003
DOI: 10.1002/app.11873
|View full text |Cite
|
Sign up to set email alerts
|

Initial droplet size distribution in miniemulsion polymerization

Abstract: ABSTRACT:The initial droplet size distribution of miniemulsions has not yet been measured. It is deduced from previous experimental results that the distribution is broad. Furthermore, the small fraction of the distribution, depending on the nonideality of the cosurfactant-monomer system, may not be stable. This may lead to a rearrangement of the distribution leading to a bimodal distribution. The stability criterion is based on the phenomenon of molecular diffusion or Ostwald ripening. Experimental proof in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…We considered this phenomena in explaining the instability seen in the miniemulsion system. [14] This analysis led to the conclusions that the initial droplet distribution should contain a significant fraction of small sized particles, which is true for a broad distribution. Further, this distribution will be bimodal when unstable.…”
Section: Stability Of the Droplet Size Distributionmentioning
confidence: 98%
See 3 more Smart Citations
“…We considered this phenomena in explaining the instability seen in the miniemulsion system. [14] This analysis led to the conclusions that the initial droplet distribution should contain a significant fraction of small sized particles, which is true for a broad distribution. Further, this distribution will be bimodal when unstable.…”
Section: Stability Of the Droplet Size Distributionmentioning
confidence: 98%
“…In recent works, the stability of the miniemulsion droplet size distribution and the nature of the initial droplet size distribution were discussed. [13,14] It was concluded that the initial droplet size distribution in miniemulsion polymerization is broad and can be bimodal. The resulting particle size distribution is also very broad and also reported to be bimodal.…”
Section: Basic Features Of Miniemulsion Polymerization Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of most interest for release experiments is that of the volume, as the release profile is mainly determined by the microcapsules that contain most of the oil in volume/ weight. The capsule size is commonly correlated using a lognormal distribution (Poncelet De Smet et al, 1989;Hollingsworth and Johns, 2003;Sood and Awasthi, 2003), Figure 2 shows a typical size distribution for MF microcapsules. From such data, the lognormal mean size (d LN ) and the lognormal standard deviation ( LN ) (see Figure 3 inset) are calculated, where d, defined as the decimal antilogarithm of d LN , is equal to D 4,3 , the volume moment mean diameter, if there is only a single size distribution.…”
Section: Effect Of the Size Polydispersitymentioning
confidence: 99%